Micro Macro Medium: Measurements of Space and Time (KULT_online, 2011)
Space and time are inseparably linked to media technologies that illustrate and measure them – and thereby generate them in the first place. The present volume addresses this constitutive relationship between media apparatuses and our perception of space and time, focusing on media-driven measuring and scaling as well as on the connected conceptual distinction between micro-level and macro-level. In this vein, the 13 essays (grouped into three sections) convincingly engage with media configurations of space and time, as well as their diagnostic and aesthetic potentials, although one would wish for an equally thorough consideration of the temporal aspects.